Mitochondrial responses to brain death in solid organ transplant - Taylor, Meredith E.; Jaishankar, Dinesh; Ho, Jessie W.; Alam, Hasan B.; Bharat, Ankit; Nadig, Satish N. (Frontiers in Transplantation, 2023)
Mitochondrial dynamics are central to the pathophysiology of cellular damage and inflammatory responses. In the context of solid organ transplantation, mitochondria are implicated in immune activation in donor organs that occurs after brain death, as they are critical to the regulation of cellular stress response, cell death, and display energetic adaptations through the adjustment of respiratory capacity depending on the cellular milieu. Mitochondrial damage activates mitochondrial systems of fission, fusion, biogenesis, and mitochondrial autophagy, or mitophagy. The mechanistic pathways as well as therapies targeting mitochondrial physiology have been studied as plausible ways to mitigate the negative effects of brain death on donor organs, though there is no summative evaluation of the multiple efforts across the field. This mini-review aims to discuss the interplay of donor brain death, mitochondrial dynamics, and impact on allograft function as it pertains to heart, lung, liver, and kidney transplants.